Armed with information: chemical self-recognition in the octopus. (December 2020) - Carls-Diamante, Sidney
Of the modalities through which self-recognition is believed to be implemented, philosophical literature on the subject is most familiar with vision and interoception. However, they are not the only ones: chemoreception is another modality that biologists have found to be a contributor to self-recognition in numerous species, of which arthropods are notable. This article aims to help address the gap between philosophical and biological literature by presenting the octopus as an example of a creature in which peripheral chemoreceptive processes appear to be a significant component of self-recognition. Building on the findings of Nesher et al. that chemical compounds in octopus skin interfere with the behaviour of its suckers, this article proffers an account of how chemoreception may contribute to self-recognition in octopuses.